Description of a new endemic species of mountain lizard from Northwestern Spain: Iberolacerta galani sp. nov. (Squamata : Lacertidae) - Arribas, Oscar; Carranza, Salvador; Odierna, Gaetano (Zootaxa, 2006)
A new species of Iberolacerta is described from the Montes de León (northwest Iberia). This new species, Iberolacerta galani sp. nov., is characterized by its relatively large size, high number of blue ocelli on the shoulders and the relatively frequent contact or near-contact between the supranasal and the first loreal scale, the fairly straight squamosal bone (only curved on its posterior part), a unique karyotype in Iberolacerta combining 2n=36 chromosomes, an L-type NOR and differentiated W and Z sex chromosomes, and unique mitochondrial DNA sequences for the cytochrome b and 12S rRNA genes. The correlation analyses show that morphology in general, but especially scalation, is strongly correlated with the amount of precipitation during the months of lizard activity, which suggests that these are not good taxonomic characters, and that other characters apparently independent of the climate like for instance osteological, karyological and DNA features are much more reliable in delimiting species boundaries in Iberolacerta. According to our phylogenetic analyses, I. galani nov. is part of a very well supported clade that originated around 2.5 mya and also includes I. monticola and I. martinezricai. Phylogeny suggests I.martinezricai might be the sister taxon to I. galani nov. from which it split approximately 2 mya, at the beginning of the Pleistocene. The clade containing I. galani nov., I. martinezricai and I. monticola was probably widely distributed across western Iberia during moderately cool and moist phases of the Pleistocene, but it was probably restricted to its present range as a result of the general temperature increase during the Holocene and competition with other lacertid lizards. Iberolacerta galani nov. is endemic to the Montes de León, where it is isolated from the other species of the “monticola-group” by the Duero and Miño-Sil Rivers, but particularly by the Bibei river valley.